Determination of period anesthetic posanestesico and constant or physiological jaguars jaguars (panthera onca) bred in captivity in the natural park zoo pucallpa under the influence of the association ketamine -xylazine - Santa Pérez Castro (2019)
The objective of the present research was to determine the ketamine - xilazine effects on the anesthetic and post anesthetic period and the physiological constants during the immobilization period of Panthera onca breed under the Parque Zoológico Natural de Pucallpa captivity conditions. For this purpose ten jaguars in Captivity from the Parque Zoológico Natural de Pucallpa weighing 40 to 67 kg were used. These were immobilized with 17.4 ± 3,97 mg/kg of ketamine clorhydrate (KC) and 0.82 ± 0.37 mg/kg of xylazine clorhydrate (XC). The initial effect and complete induction time, rectal, temperature, cardiac and respiratory frequency and recovery time were recorded. The initial effect time was 6.9 ± 2.88 minutes and the time of complete induction was 12.9 ± 6.19 minutes. The rectal temperature during immobilization time was from 38.5 to 41.2 oc. The cardiac and respiratory frequency was from 64 to 116 bits/minute and from 26 to 36 respirations per minute respectively. The recuperation time was 151.1 ± 17.46 minutes. Conclusivelly, the anesthetic and post anesthetic period and physiologycal constants of Panthera onca breed under the Parque Zoológico Natural de Pucallpa captivity conditions, maintained into normal ranges under the ketamine-xilazine association effect.